Lipid Droplet‐Targetable Fluorescence Guided Photodynamic Therapy of Cancer Cells with an Activatable AIE‐Active Fluorescent Probe for Hydrogen Peroxide. Issue 20 (9th August 2020) - Jiang, Guoyu; Li, Chunbin; Liu, Xiang; Chen, Qingqing; Li, Xiaokang; Gu, Xinggui; Zhang, Pengfei; Lai, Qingfang; Wang, Jianguo
Abstract: Fluorescence guided photodynamic therapy (FL‐PDT) offers the great opportunity for realizing personalized medicine in the treatment of cancer. Aggregation‐induced emission luminogens (AIEgens) with efficient emission and reactive oxygen species (ROS) generation even in the aggregated state are the ideal FL‐PDT photosensitizers to overcome the quenched fluorescence and ROS that traditional photosensitizers faced in PDT. Moreover, considering the higher levels of H2 O2 in cancer cells than in normal cells and the fact that lipid droplet (LD) accumulation correlates to the enhanced survival rate of cancer cells in hypoxic conditions, it will be very interesting and rewarding to develop a LD‐targeted, H2 O2 activatable AIE‐active photosensitizer for FL‐PDT. Thereafter, a LD‐targeted fluorescent probe TPECNPB is fabricated for H2 O2 ‐activatable fluorescence guided PDT of cancer cells. AIE‐active TPECNPB exhibits the unique features of large Stokes shift (175 nm), superior photostability, and excellent selectivity toward H2 O2 . TPECNPB is able to selectively accumulate in LD and is activated by endogenous H2 O2 for light‐up bioimaging in live MCF‐7 cells. In addition, H2 O2 ‐activatable singlet oxygen generation and PDT of cancer cells has also been successfully implemented with TPECNPB. These prominent parameters would make TPECNPB a powerful toolbox for H2 O2 ‐activatable and LD‐targetable fluorescence guided PDT of cancer cells. Abstract : A lipid droplet (LD) targeted AIE‐active fluorescent probe TPECNPB has been synthesized for H2 O2 ‐activatable fluorescence guided photodynamic therapy (PDT) of cancer cells. TPECNPB exhibits large Stokes shift, superior photostability, and excellent selectivity toward H2 O2 . TPECNPB enables real‐time imaging of H2 O2 in LD of live cells. H2 O2 ‐activatable singlet oxygen generation and PDT of cancer cells are also realized by using TPECNPB.